Does Dexamphetamine Cause Addiction? A Narrative Review - Hazer Khalifa; Emily J. Hibbert; Natalie Gauci; Alison Poulton (Psychoactives)
Dexamphetamine (DEX) is widely used in treatments, but concerns persist about its potential for addiction. This review aimed to assess the risks of DEX addiction by examining the existing literature. Originally planned as a systematic review, it was adjusted to a narrative review due to a lack of qualifying studies. A search of the literature on addiction to DEX was conducted on three databases including PubMed, Scopus, and Embase. Seven articles consisting of three reviews and four papers with original data were identified and reviewed. In total, four poorly documented cases of possible DEX addiction were found. The commonly cited papers on prescription DEX addiction did not hold up to scrutiny. Overall, the evidence that DEX is addictive is limited and inconclusive, highlighting the need for more rigorous research to clarify its true addiction risk.